ANALISIS BUKU: KEUTUHAN TAHAPAN PEMBELAJARAN IPA DENGAN PENDEKATAN SAINTIFIK PADA BUKU SISWA SEKOLAH DASAR KURIKULUM 2013 - Kintan Limiansih (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2020)
This study aimed to know the integrity of the learning stages with a scientific approach in the book of elementary school students curriculum specialized in the field of IPA 2013. Analysis of the book is based on the importance of a scientific approach to development, the importance of books as learning guides, and previous research gaps. This research is a descriptive research in which researchers describe the activities in the book according to the facts. The books that analyzed are primary student books grade 1, 2, 3, 4 and 5. Analyses were performed by using the instrument of accession rubric analysis that has been processed by researchers. From the analysis, obtained information that, there are no activites in science which apply the learning stages with the full scientific approach intact (5 stages). So this book must be repaired by the goverment ant teacher. Besides that, teachers need to do additional activities in order to maximize learning with scientific approach.